Phytochemical and Anti-Sickling Properties of Aqueous Extract of Pennisetum purpureum Schumach (Elephant Grass) Shoots - Onwubiko U. I.; Imo C.; Onwubiko G. N.; Boyi R.N; Dawoye Y.; Galadima A. O.; Sanusi A.; Solomon J. E. (Darul Yasin Al Sys, 2026)
Sickle cell disease remains a major haematological disorder associated with haemoglobin S polymerization and erythrocyte sickling, highlighting the need to explore plant-derived compounds with potential anti-sickling activity. This study aimed to determine the anti-sickling potential of the aqueous extract of young shoots of Pennisetum purpureum using microscopy after 2% sodium metabisulphite-induced sickling of sickle red blood cells. The findings showed that Pennisetum purpureum extract significantly reversed many sickled cells to normal-shaped cells, with the percentage reversal depending on both concentration and exposure time. At 250 μg/mL, sickle cell reversal was 88.82% at 0 min, 86.09% at 30 min, and 85.19% at 60 min, whereas the control without extract showed no reversal. At 500 μg/mL, the reversal percentages were 80.14% at 0 min, 92.27% at 30 min, and 90.51% at 60 min. At 1000 μg/mL, reversal increased from 79.13% at 0 min to 94.82% at 30 min and 96.50% at 60 min. Phytochemical analysis indicated the presence of aromatic and alkylic compounds, including quercetin, epicatechin, resveratrol, vanillic acid, ellagic acid, and kaempferol. These compounds may contribute to anti-sickling activity through hydrophobic interactions that interfere with haemoglobin S polymerization and stabilize the hydrophobic erythrocyte lipid bilayer membrane. This study contributes to phytomedicine and sickle cell research by demonstrating the potential of Pennisetum purpureum young shoot extract as a source of bioactive compounds with anti-sickling properties, although further biochemical, toxicological, and clinical validation is required.